2021
DOI: 10.3389/fpls.2020.620377
|View full text |Cite
|
Sign up to set email alerts
|

Functional Analysis of the Phosphate Transporter Gene MtPT6 From Medicago truncatula

Abstract: Phosphorus is one of the essential macronutrients required by plant growth and development, but phosphate resources are finite and diminishing rapidly because of the huge need in global agriculture. In this study, 11 genes were found in the Phosphate Transporter 1 (PHT1) family of Medicago truncatula. Seven genes of the PHT1 family were available by qRT-PCR. Most of them were expressed in roots, and almost all genes were induced by low-phosphate stress in the nodule. The expression of MtPT6 was relatively high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 41 publications
0
28
0
Order By: Relevance
“…It has been reported that there are 11 PHT1 transporters in M. truncatula ( Cao et al, 2020 ). We identified another two members (Mt4g083960 and Mt5g068140) by searching Ensemblplants.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported that there are 11 PHT1 transporters in M. truncatula ( Cao et al, 2020 ). We identified another two members (Mt4g083960 and Mt5g068140) by searching Ensemblplants.…”
Section: Resultsmentioning
confidence: 99%
“…MtPT4 is highly expressed in mycorrhizal roots, responsible for Pi acquisition from arbuscules ( Harrison et al, 2002 ). It is also expressed in plant root tip in the absence of the arbuscular mycorrhizal (AM) fungus and modulates root branching, whereas it does not significantly affect Pi accumulation in plants without AM symbiosis ( Cao et al, 2020 ). Recently, MtPT6 was reported to be involved in Pi uptake by heterologous expression of MtPT6 in Arabidopsis pht1;1 or pht1;4 mutant.…”
Section: Introductionmentioning
confidence: 99%
“…8). Numerous PT homologues are found to be enhanced by P deficiency in soybean [23], rice [47] and Medicago (Medicago truncatula) [48]. For example, in Arabidopsis, the transcripts of two Pi transporters (Pht1;1 and Pht1;4) are significantly increased in low P-treated roots, which are involved in Pi uptake [49,50].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, different combinations of Pi transporters and Pi stress response factors form diverse regulatory networks in the N fixation and non-fixation zones to maintain Pi homeostasis in response to both systemic and local Pi availability for efficient symbiotic N fixation in soybean nodules ( Lu et al, 2020 ). Eleven members of the PT1 family have been identified in M. truncatula , and most of them were highly expressed under conditions of low Pi ( Cao et al, 2020 ). In addition to root epidermis, cortex, vascular tissues, and root tips, MtPT6 was also expressed in nodules, suggesting that it may play a role in Pi uptake from soil and transporting Pi to nodules from other tissues ( Cao et al, 2020 ).…”
Section: The Role Of Phosphate Signaling and Transport In Symbiotic Nitrogen Fixationmentioning
confidence: 99%
“…Eleven members of the PT1 family have been identified in M. truncatula , and most of them were highly expressed under conditions of low Pi ( Cao et al, 2020 ). In addition to root epidermis, cortex, vascular tissues, and root tips, MtPT6 was also expressed in nodules, suggesting that it may play a role in Pi uptake from soil and transporting Pi to nodules from other tissues ( Cao et al, 2020 ). Pi deficiency induces the expression of purple acid phosphatase (PAPs) in root nodules, which leads to an enhanced acquisition and utilization of P in root nodules ( Li et al, 2017 ; Wang et al, 2020e ).…”
Section: The Role Of Phosphate Signaling and Transport In Symbiotic Nitrogen Fixationmentioning
confidence: 99%